Frequency and cost of live vaccines administered too soon after prior live vaccine in children aged 12 months through 6 years, 2014–2017. Issue 46 (31st October 2019) - Kirtland, Karen A.; Lin, Xia; Kroger, Andrew T.; Myerburg, Stuart; Rodgers, Loren
Abstract: Objective: To identify number of children who received live vaccines outside recommended intervals between doses and calculate corrective revaccination costs. Methods: We analyzed >1.6 million vaccination records for children aged 12 months through 6 years from six immunization information system (IIS) Sentinel Sites from 2014–15 when live attenuated influenza vaccine (LAIV, FluMist® Quadrivalent) was recommended for use, and from 2016–17, when not recommended for use. Depending on the vaccine, insufficient intervals between live vaccine doses are less than 24 or 28 days from a preceding live vaccine dose. Private and public purchase costs of vaccines were used to determine revaccination costs of live vaccine doses administered during the live vaccine conflict interval. Measles, mumps, rubella (MMR), varicella, combined MMRV, and LAIV were live vaccines evaluated in this study. Results: Among 946, 659 children who received at least one live vaccine dose from 2014–15, 4, 873 (0.5%) received at least one dose too soon after a prior live vaccine (revaccination cost, $786, 413) with a median conflict interval of 16 days. Among 704, 591 children who received at least one live vaccine dose from 2016–17, 1, 001 (0.1%) received at least one dose too soon after a prior live vaccine (revaccination cost, $181, 565) with a median conflict interval of 14 days. The live vaccine most frequently administered outside of the recommended intervals was LAIV from 2014–15, and varicella from 2016–17. Conclusions: Live vaccine interval errors were rare (0.5%), indicating an adherence to recommendations. If all invalid doses were corrected by revaccination over the two time periods, the cost within the IIS Sentinel Sites would be nearly one million dollars. Provider awareness about live vaccine conflicts, especially with LAIV, could prevent errors, and utilization of clinical decision support functionality within IISs and Electronic Health Record Systems can facilitate better vaccination practices.